Successful Management of Acute Catastrophic Juvenile Vaginal Bleeding in Glanzmann’s Thromboasthenia by Uterine Tamponade: A Case Report and Review of The Literature - Nazli Hossain; Tahir S. Shamsi; Adeel Feroz (Case Reports in Hematology)
Glanzmann’s thromboasthenia (GT) is a rare platelet disorder, due to membrane defects involving glycoprotein GP IIb/IIIa complex. Symptoms appear in infancy with episodes of bruising, gingival bleeding, epistaxis, or at the time of menarche acute episode of uterine bleeding. Hormonal therapy and antifibrinolytic agents are first-line treatment. Platelet transfusion is given to control hemorrhage when medical treatment fails. However, repeated transfusions may result in development of platelet refractioness, due to development of antibodies against membrane glycoprotein. Activated recombinant FVII is licensed for use in acute control of bleeding in GT. Here we report a case of acute juvenile uterine bleeding at menarche, which responded successfully to uterine tamponade. To our knowledge, this is the first case report on use of balloon tamponade for control of acute catastrophic juvenile bleeding at menarche.